THE IMPULSE OF COURAGE IN STEPHEN CRANE’S THE RED BADGE OF COURAGE : AN INDIVIDUAL PSYCHOLOGICAL APPROACH - TRISTYANINGRUM , ENDAH BINTARI (2007)
In this research, the researcher attempts to find out how the impulse of courage influences Henry Fleming’s personality development. The objective of the research is to analyze the novel based on the individual psychological approach proposed by Alfred Adler. This research belongs to qualitative research, which employ textual data. The data sources are taken from two sources, namely the text of the novel as primary data source and the other materials related to the problem of the study as secondary data source. The method of data collection is library research and the technique of data analysis is descriptive. The result of the research is as follows. Firstly, the structural element of the novel presents a solid unity. Secondly, the individual psychological analysis shows that the impulse of courage of Henry Fleming comes from his fictional finalism and it’s supported by his inferiority feeling. It makes his strive to reach the superiority and power in emerging the impulse of courage in the real battlefield but his strives to superiority goes in wrong direction. In the end, it can be concluded that the impulse of courage cannot find happiness without balanced positive direction. Finally, Henry gets his impulse of courage after overcome the fearless and fight bravely in the battlefield.